Seasonal drivers of productivity and calcification in the coral Platygyra carnosa in a subtropical reef - Dellisanti, Walter; Chung, Jeffery T. H.; Yiu, Sam K. F.; Tsang, Ryan Ho Leung; Ang, Put; Yeung, Yip Hung; Qiu, Jian-Wen; McIlroy, Shelby E.; Wells, Mark L.; Wu, Jiajun; Chan, Leo Lei (Frontiers in Marine Science, 2023)
Scleractinian corals are increasingly subjected to local stressors combined with global changes. In subtropical areas, corals exhibit metabolic plasticity and resilience in response to variability and extremes in local temperature, salinity, and light; however, the physiological mechanisms by which corals acclimate or adapt to these changing conditions remain disputed. We assessed the physiological status of the coral Platygyra carnosa during a two-year in situ monitoring survey. To obtain metabolic rates (respiration and photosynthesis), photochemical efficiency (Fv / Fm), and biocalcification measurements, non-invasive techniques such as underwater respirometry, Pulse Amplitude Modulated (PAM) fluorometry, total alkalinity measurements, and digital photography were used. Our findings show clear seasonality in water quality parameters, which affected coral health. Elevated temperatures during the summer were below the maximum monthly mean (< 31°C) but reduced the energetic productivity (Pg / R) of corals. Fluctuations in salinity (25–38 ppt) and pH (7.65–8.44) were linked to rainfall and reduced calcification rates. The conditions during the spring were favorable for coral metabolism and calcification. Overall, our research demonstrates that the metabolic plasticity of P. carnosa in response to shifts in seawater quality allows this species to survive ongoing environmental change. Our in situ observations provide fundamental insights into coral response mechanisms under changing environmental conditions and contribute to projections of coral health under future scenarios of global change.